Effects of glycowithanolides from Withania somnifera on morphine‐induced inhibition of intestinal motility and tolerance to analgesia in mice - Ramarao P.; Rao K.T.; Srivastava R.S.; Ghosal S. (My University, 2025)
Effects of glycowithanolides (Ws, 10–150 mg/kg, i.p.), consisting of sitoindosides VII‐X, in combination with withaferin‐A, from Withania somnifera, in Swiss mice were evaluated on (i) morphine‐induced inhibition of gastrointestinal tract (GIT) transit and (ii) development of tolerance to morphine‐induced analgesia. Pretreatment with Ws significantly reversed the morphine (5 mg/kg, s.c.)‐induced inhibition of GIT transit at all doses. Ws (100 mg/kg, i.p., o.d., for 10 days) significantly inhibited the development of tolerance to morphine‐induced analgesia. Ws per se did not influence the intestinal motility nor did it produce any perceptible analgesic effect. The present and earlier findings with Ws suggest its potential in alleviating the adverse effects of morphine and the attendant immunodepression. Copyright © 1995 John Wiley & Sons, Ltd.